ASSESSMENT OF GENOTOXIC PROPERTIES OF PROLINE-ENRICHED POLYPEPTIDE IN VIVO BY COMET ASSAY (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
The genotoxicity of proline enriched polypeptide (PRP-1) was estimated in mice leucocytes depending on its action time in vivo by Comet assay. A high level of DNA damages compared with the control variants was revealed. As well as a small amount of DNA damage is revealed in comparison with the control and there is a tendency for decreasing the level of damage in DNA with the lapse of time after the introduction of PRP-1. Taking into consideration the low genotoxicity of PRP-1, we can conclude the safety of this drug demonstrated in the applied test-system.
Keywords: genotoxicity; Comet assay; test-system; mice leucocytes; level of damage in DNA